The Intersectional Approach : Transforming the Academy through Race, Class, and Gender - Guidroz, Kathleen; Berger, Michele Tracy, 1968- (Book collections on Project MUSE., 2009)
Intersectionality, or the consideration of race, class, and gender, is one of the prominent contemporary theoretical contributions made by scholars in the field of women's studies that now broadly extends across the humanities, social sciences, and natural sciences. In 18 essays, contributors here look specifically at gender inequalities related to globalization, health, motherhood, sexuality, body image, and aging. Together, these essays provide a critical overview of intersectionality, highlight new theoretical and methodological advances, and make a strong case for the continued use of the.